2018
DOI: 10.1111/asj.13024
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification for bovine embryos with low‐quality grade

Abstract: This study was conducted to examine the utility of vitrification for bovine embryos with low-quality grade, and simple cryoprotectants dilution method for practitioners. In Experiment 1, survival of frozen embryos was compared with that of vitrified embryos using minimum volume cooling (MVC). Then, vitrified embryos were used to confirm the optimum sucrose concentration in Experiment 2. The survival rates of embryos that had been vitrified following diluted cryoprotectants with the one-step in-straw method wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…When using vitrification technology in veterinary practice, a practical approach is needed for the warming of vitrified embryos so that embryos can be directly and easily transferred to the uterus. Thus far, there have been several attempts to replace successive dilution steps with one-step in-straw cryoprotectant dilution [3][4][5][6][7][8][9][10][11][12][13][14][15] However, in some of these procedures, in-straw embryo warming requires more than one dilution step and the proper handling of the carrier system, thus demanding more accuracy when these techniques are to be used in the field by embryo-transfer practitioners [7,9,10,12]. Using the VitTrans device designed by our group, IVP embryos are easily warmed/diluted in-straw for their transfer to recipient females in field conditions [16].…”
Section: Introductionmentioning
confidence: 99%
“…When using vitrification technology in veterinary practice, a practical approach is needed for the warming of vitrified embryos so that embryos can be directly and easily transferred to the uterus. Thus far, there have been several attempts to replace successive dilution steps with one-step in-straw cryoprotectant dilution [3][4][5][6][7][8][9][10][11][12][13][14][15] However, in some of these procedures, in-straw embryo warming requires more than one dilution step and the proper handling of the carrier system, thus demanding more accuracy when these techniques are to be used in the field by embryo-transfer practitioners [7,9,10,12]. Using the VitTrans device designed by our group, IVP embryos are easily warmed/diluted in-straw for their transfer to recipient females in field conditions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the rates of IVF using spermatozoa with a shorter life span and/or damage were also improved when intracytoplasmic sperm injection was introduced into the IVEP industry [40, 41]. Recently, vitrification, an additional technique related to MOET, has been used as a method for preserving bovine embryos of low-grade quality [42, 43], although the pregnancy rate after cryopreservation depends on the quality of the embryos. This technical improvement could contribute to increases in female embryo and calf production by IVEP with X-sorted semen and FGS oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…So far, there have been several attempts to replace successive dilution steps with one-step in-straw cryoprotectant dilution [3][4][5][6][7][8][9][10][11][12][13][14]. However, in some of these procedures, in-straw embryo warming requires more than one dilution step and proper handling of the carrier system, demanding more accuracy when these techniques are to be used in the eld by embryo-transfer practitioners [7,9,10,12]. Using the device VitTrans designed by our group, IVP embryos are easily warmed/diluted in-straw for their transfer to recipient females in eld conditions [15].…”
Section: Introductionmentioning
confidence: 99%